Challenges for Monte Carlo generators - Reuter Jürgen (EPJ Web of Conferences)
This contribution lists challenges of Monte Carlo event generators for future lepton, especially linear colliders. A lot of the recent development benefits from the achievements at the Large Hadron Collider (LHC), but several aspects are unique for lepton colliders like beam simulation, polarization, electroweak higher order corrections and resummed QED corrections. We will describe the status of multi-purpose event generators and specialized codes and outline the challenges for these tools until such a collider starts data taking.